Astragalus mongholicusbunge and Angelica sinensis botanical drug decoction mitigates lung inflammation through NOX4/TGF-β1/SMAD3 signaling - Yang, Zhifeng; Chang, Yuqian; Zhou, Tong; Sui, Wenwen; Dai, Ping; Wei, Yuan; Wang, Jia-Sheng; Zhou, Jun; Wen, Chengli; Zhang, Haidong (Frontiers in Pharmacology, 2025)
IntroductionAstragalus mongholicus bunge and Angelica sinensis are botanical drugs rich in beneficial nutrients and health-promoting metabolites. Their roots can be decocted to a botanical drug decoction “Danggui Buxue Tang (DBT),” demonstrating human anti-inflammatoryMethodsHere, we evaluate the mitigating function of DBT on lung inflammation and early fibrosis in a rat model. The model was established by tracheal dripping of silica suspension for 28 days. Positive intervention effects of DBT were observed in a dose-dependent manner after consecutive gavage of DBT (1.9, 3.8, and 7.6 g/kg·bw/d) for 28 days and 42 days. To explore the underlying molecular mechanism. DBT metabolites were profiled using a liquid chromatograph-mass spectrometer and the Chemspider database.ResultsLung inflammation and fibrosis were confirmed using functional tests and histopathologic analysis. Metabolite target analysis identified nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 4 (NOX4) as a key target of DBT in regulating pulmonary fibrosis. Gene ontology (GO) analysis estimated that oxidative stress, inflammatory response, myofibroblast differentiation, and extracellular matrix (ECM) deposition were the major target pathways of DBT. KEGG analysis found that DBT might modulate pulmonary fibrosis through the transforming growth factor-β (TGF-β) pathway. GO chord and signaling pathway maps revealed that NOX4 contributes to oxidative stress, inflammatory response, and TGF-β pathway regulation. The in vivo analyses confirmed that DBT significantly reduces NOX4 protein expression, inhibits oxidative stress and inflammatory responses, and reduces TGF-β1, p-SMAD3, fibronectin 1 (FN1), and smooth muscle actin (α-SMA) protein expression.DiscussionThese findings demonstrate the lung-protecting function of DBT in a rat model and identify critical target proteins associated with the underlying mechanism.